Adaptasi dan Validasi Alat Ukur Kepuasan Kebutuhan Dasar Psikologis pada Guru - Utomo, Hanggara Budi; Putri, Raissa Dwifandra (Flourishing Journal, 2025)
Teachers' interest and desire and motivation to teach will arise if there is an experience of basic psychological need satisfaction. This study aims to adapt and validate the Basic Psychological Need at Work developed by Ilardi, in order to obtain a valid and reliable measuring instrument to measure the satisfaction of the basic psychological needs of the Indonesian version of teachers in East Java. The adaptation process was carried out using guidelines from the International Test Commission in 2017. The validation process is carried out by testing content validity using content validity analysis and construct validity using confirmatory factor analysis. The respondents were 108 elementary school teachers in Kediri, Blitar, Nganjuk, and Tulungagung. Based on the results, it can be seen that the measurement model of the psychological basic needs satisfaction construct explains the existence of a good goodness of fit. In addition, the composite reliability value of the measuring instrument is between 0.74-0.93, and the average variance extracted value is in the range of 0.64-0.92. The results of this study indicate that the Basic Psychological Need at Work measuring instrument is a valid and reliable measuring instrument for measuring basic psychological need satisfaction in teachers in Indonesia, especially in East Java